POTENSI DAN TANTANGAN SUMBERDAYA MANUSIA DALAM IMPLEMENTASI KEBIJAKAN PELAYANAN PERIZINAN ONLINE PADA DPMPTSP KOTA MEDAN - Nurhafsyah Daulay; Ermi Girsang; Putranto Manalu (GEMA PUBLICA, 2021)
This study aims to analyze the existence of the human resource dimension in the implementation of the healthcare facility licensing policy implemented by the Medan City Investment and One Stop Service (DPMPTSP) in 2020. This study uses a qualitative approach by utilizing in-depth interviews and observations as the main data sources. The results of the study indicate that the transition of facility licensing services from conventional methods to online-based services or e-government is a challenge in policy implementation, especially related to the human resource dimension. The human resources for implementing the online licensing service policy in quantity are seen as still inadequate in addition to the technical competence of existing employees who have not fully supported the implementation of the electronic and online-based services. Keywords: Policy Implementation; Licensing Services; E-Government; Human Resources